Real time parameter estimation for power quality control and intelligent protection of grid-connected power electronic converters - Sumner, M.; Abusorrah, Abdullah; Thomas, David W.P.; Zanchetta, Pericle (Institute of Electrical and Electronics Engineers, 2014)
This paper presents a method to identify power system impedance in real-time using signals obtained from grid- connected power electronic converters. The proposed impedance estimation has potential applications in renewable/distributed energy systems, STATCOM, and solid state substations. The method uses wavelets to analyze transients associated with small disturbances imposed by power converters and determine the net impedance back to the source. A data capture period of 5ms is applied to an accurate impedance estimation which provides the possibility of ultra fast fault detection (i.e. within a half cycle). The paper describes how the proposed method would enhance the distributed generation operation during faults.